PEMELIHARAANIKANBERONANG,Siganus gutatus SEBAGAIBIOKONTROL PERKEMBANGANLUMUT,Chaetomorpha sp. DANEnteromorpha intestinalis DITAMBAK =THE REARINGOF RABBITFISH, Siganus gutatus AS BIOCONTROLOF THE GREEN ALGAE, Chaetomorph - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The aim of this research was to control the growth of green algae (Chaetomorpha sp. and Enteromorpha intestinalis) by rabbitfish (Siganus gutatus) reared in brackishwaterpondsat different stocking density.The research was conducted in the Research Station of Research Institute for Coastal Aquaculture, Marana, Maros, South Sulawesi for 100 days. Nine brackishwater ponds hi the size 100 m2(3 ponds), 125 m2(3 ponds) and 150m2(3 ponds) respectively with the green algae growth were used in this research. Group randomized design was used in this research. This research used three stocking density of rabbit fish in triplicates that were (A) 20 ind/100m2, (8) 30 ind/100 m2(40 ind/125 m2),and (G) 40 ind/100m2(60 ind/150 m2),respectively. The rabbit fish used in this research were 9.1:!:.0.8 cm in length and 15:!:.0.6 9 in body weight. The monitored variables were body length and weight, survival rate and water quality. The result showed that the effect of stocking density was not significantly different on the growth of body length and weight and survival rate of rabbit fish reared in brackishwater pond (P>0.05), but significantly different on the productivity of rabbit fish (P